(untitled) (Economics and region, 2025)
Innovation can provide new opportunities to improve project efficiency. The current study is devoted to substantiating the importance of innovation and the feasibility of using intellectual analysis tools in project management practice. To take into account the peculiarities of innovation, there is a need to clarify the concept of evaluation and selection of priority project decisions. The result of project evaluation is their classification and diagnostics according to the selected goals and development priorities of the relevant hierarchical level. The success of innovative activity depends on such factors as: access to resources (financial, material, information); regulatory and legal support for the creation, commercialization and legal support of innovations; availability of qualified and motivated personnel. Given the rapid development of digital technologies in all spheres and industries, information support is positioned as an integrated computer and telecommunication system that widely uses intelligent analysis tools not only for data processing but also for making management decisions at any level. The practical implementation and achievement of the goals of innovative development projects is ensured by the synergy of knowledge, tools, principles, and processes of project-oriented management. The authors have systematized the components of project-oriented management, highlighting the market, regulatory, and iterative components. An innovative and intelligent decisions is the application of an iterative approach, according to which the set of project management technologies and tools are adjusted as updated data becomes available. This approach will enhance responsibility for decisions made at each hierarchical level. The scope of application and tools for intelligent analysis at the micro level have been agreed upon. Emphasis is placed on shifting the focus from managing a specific project to managing a portfolio of projects at the business unit, industry, and regional levels. The specifics of such management require the development of a new methodological approach and a significant transformation of existing models for evaluating the effectiveness of programs, projects and project portfolios.